2021
DOI: 10.1088/1361-6668/abc73d
|View full text |Cite
|
Sign up to set email alerts
|

First demonstration of high current canted-cosine-theta coils with Bi-2212 Rutherford cables

Abstract: Future high energy physics colliders could benefit from accelerator magnets based on high-temperature superconductors, which may reach magnetic fields of up to 45 T at 4.2 K, twice the field limit of the two Nb-based superconductors. Bi2Sr2CaCu2O8-x (Bi-2212) is the only high-T c cuprate material available as a twisted, multifilamentary and isotropic round wire. However, it has been hitherto unclear how an accelerator magnet can be fabricated from Bi-2212 round wires and whether high field qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Since then, various authors have further developed and demonstrated the concept [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. The MDP is developing high-field CCT dipole magnet technology for Nb 3 Sn [41][42][43] and two high-temperature superconductors: Bi 2 Sr 2 CaCu 2 O 8+x [44][45][46][47] and rebco [19,48,49].…”
Section: Magnet Configurationmentioning
confidence: 99%
“…Since then, various authors have further developed and demonstrated the concept [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. The MDP is developing high-field CCT dipole magnet technology for Nb 3 Sn [41][42][43] and two high-temperature superconductors: Bi 2 Sr 2 CaCu 2 O 8+x [44][45][46][47] and rebco [19,48,49].…”
Section: Magnet Configurationmentioning
confidence: 99%
“…In collaboration with industry partners, the U.S. Magnet Development Program (MDP) is developing magnet technology for both conductors [3][4][5][6][7][8][9][10][11]. * Authors to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The last tenyears have seen a renewed interest in the Bi-2212 wire that has pushed several research groups towards performance optimization [1][2][3][4][5][6][7]. Today, we can say that the Bi 2 Sr 2 Ca 2 Cu 2 O x (Bi-2212) has become a true prospect for high magnetic field magnets above 18-20 T, going beyond the practical limit of state-of-the-art Nb 3 Sn conductors [8][9][10]. * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%